A comparative study of thermal kinetics and combustion performance of Al/CuO, Al/Fe2O3 and Al/MnO2 nanothermites. (June 2020) - Song, Jiaxing; Guo, Tao; Yao, Miao; Chen, Jialin; Ding, Wen; Bei, Fengli; Mao, Yiming; Yu, Zhongshen; Huang, Junyi; Zhang, Xiaonan; Yin, Qin; Wang, Shuo
Abstract: The performance of energetic materials is mainly reflected in two aspects, thermal performance and combustion performance. To figure out the differences in reaction performance, in this paper, thermal and combustion properties of Al/CuO, Al/Fe2 O3 and Al/MnO2 nanothermites were studied respectively by thermal analysis and fast heating wire experiments. According to the thermal analysis, the exothermic peak temperature points of Al/MnO2, Al/CuO, Al/Fe2 O3 nanothermites were 552.1 °C, 563.1 °C and 565.3 °C, respectively, while the sequence of activation energy calculated from low to high was Al/Fe2 O3, Al/CuO, Al/MnO2 nanothermites. By the way, the values of Al/CuO and Al/Fe2 O3 nanothermites showed little difference in temperature and activation energy. The ignition energy characterized by direct current had little difference among them, and the sequence from low to high was Al/MnO2, Al/Fe2 O3, Al/CuO nanothermites, corresponding to 1.169 A, 1.214 A and 1.221 A, respectively. As for burning rate, Al/CuO burnt the fastest clearly while the Al/Fe2 O3 burnt the longest. In terms of combustion performance, Al/CuO and Al/MnO2 were basically the same, with little splash of sparks, and the concentrations of combustion energy were better. The combustion phenomenon of Al/Fe2 O3 nanothermite was quite unique with a large number of scattered sparks and poor energy concentration. Finally, the intrinsic reasons for above different phenomena of these three nanothermites were analyzed and discussed. Highlights: Sequence of exothermic peaks was Al/MnO2, Al/CuO, Al/Fe2 O3 nanothermites. Sequence of activation energy from was Al/Fe2 O3, Al/CuO, Al/MnO2 nanothermites. Fastest burning was Al/CuO nanothermite, while the longest was Al/Fe2 O3 . Combustion phenomenon of Al/CuO was similar to that of Al/MnO2 . Al/Fe2 O3 produced lots of scattered sparks with poor energy concentration.